THE CONCEPT OF RESPECT AND THE HARMONY OF STYLISTIC DEVICES (Scientific journal of the Fergana State University, 2025)
The concept of respect holds a significant place in the culture and values of every society. This article examines the interplay between the concept of respect and stylistic devices in the Uzbek language. Various forms of expressing respect through linguistic and stylistic tools are analyzed. The study utilizes contemporary Uzbek literary texts and media materials. The role of stylistic devices in cultural communication is explored within the framework of Brown and Levinson’s politeness theory. This article provides new insights for linguistic research. The concept of respect is one of the crucial phenomena in interpersonal relationships. This article explores the features of expressing respect in different languages and the role of stylistic devices in this process. Various linguistic units related to respect in Uzbek, Russian, and English, along with their contexts of use, are analyzed. Special attention is given to stylistic devices such as metaphor, epithet, and polite lexical expressions that play a key role in conveying respect. Additionally, the manifestations of respect in different cultural contexts, along with their similarities and differences, are highlighted. The findings of the study provide a deeper understanding of the uniqueness of the concept of respect across languages and cultures and how this notion is expressed through linguistic and stylistic means.